Prevalence of Sleep Problems and Its Association With Preterm Birth Among Kindergarten Children in a Rural Area of Shanghai, China - Wang, Ruiping; Chen, Jun; Tao, Liqun; Qiang, Yan; Yang, Qing; Li, Bin (Frontiers in Pediatrics, 2022)
Introduction: Healthy sleep in children is critical for their physical and mental health. Although growing evidence indicates the linkage between preterm birth and the neural network that regulates sleep architecture, findings on the association between preterm birth and sleep problems among children are still contradictory. The prevalence of sleep problems and its association with preterm birth in children is especially limited in Shanghai, China. Methods: We selected 8, 586 children aged 3-6 years and their mothers in Shanghai. Data was collected by questionnaire interview among mothers with informed consent signed ahead. Six sleep problems (insufficient sleep, sleepwalk, nightmare, snore, grind teeth and cry in sleep) were selected in this study. SAS 9.4 was used for data analysis, and p <0.05 was considered as statistically significant. Results: In this study, the prevalence of preterm birth was 9.88% (848/8,586), with a higher prevalence in boys (10.62%). The prevalence of sleep problems was 89.81% among kindergarten children, with 62.50% for snore, 50.35% for grind teeth, 49.20% for cry in sleep, 41.18% for nightmare, 11.67 for sleep deprivation and 4.44% for sleepwalk. The age of children, family income and mothers’ education were associated with the prevalence of sleep problems in children. Logistic regression indicated that sleep problems in preterm children was comparable with full-term children [Odd Ratio=1.13, 95% Confidence Interval (0.89-1.45)]. Conclusions: Sleep problems was prevalent among children aged 3-6 years in Shanghai, and preterm birth was not associated with sleep problems in children. We recommend that parents should create limit setting in home, cultivate similar child rearing attitude and beliefs among family members, and encourage children to go to bed earlier.